Model-View-Controller Design System of Motorcycle Damage Detection Using Forward Chaining Method - Rismayani Rismayani; Muhammad Wahinuddin Tahir; Muhammad Darwis; Nurani Nurani; Martina Pineng (Journal of Information Technology and Its Utilization, 2023)
This study aims to design a motorbike damage detection system using the forward chaining method with a view controller model that can be run on a mobile-based system. Dealers and motorbike service providers receive and fulfil customer requests for motorbike service services. Mechanics who service vehicles still use conventional methods to check vehicle damage by scanning the paper (form). There is a list ofvehicle damage. This method takes quite a long time, and it is not sure that the problem will be resolved quickly. The research method used is forward chaining, and the model used is the Model View Controller, which separates data from the display by processing it. The result of this research is that with a motorbike damage detection system, mechanics from dealers and service areas do not have to carry out initial checks manually but instead use a system with a view controller model and initial check results. Detection can also be determined by applying the forward chaining method. Based on functional testing of the system using a black box, valid results were found; then, for logic testing using the forward chaining method, the results were free from logical errors.